Research and Publication ethics - Upendra Pratap Singh and others; SINGH (Upendra Pratap); AHLAWAT (Sakshi); SHARMA (Sushma) (New Delhi Sultan Chand and Sons, 2024)
This book is for the UGC-approved course on research and publication ethics as a prerequisite course for Ph.D. students. The key areas covered in the book are as follows: Introduction to the concept of philosophy and ethics in relation to research The history and evolution of ethics in research for a better understanding of the importance of ethics in research. Ethical principles researchers must follow and abide by at every stage of research, beginning from the planning stage to the data analysis and writing and publication stage. The various regulatory bodies and the guidelines set by them to be followed by researchers. The unethical practices in research and its implications for all the personnel involved in the research process The best practices in research and publication given by the Committee of Publication Ethics The concept of Open Access in Publishing, its advantages and the various sources for Open Access Journals. Predatory Publishing as a detrimental practice for research and publication. Ways to manage and deal with research misconduct, complaints and appeals in case of misconduct, explained well with the help of case studies. Various journal finder/suggestion tools, their features and applications in the process of publication. The concept of indexing and metrics in research, their calculation and application. The importance of databases in research, their source and features, for the researchers to choose the most suitable database for their study.
Keywords: Research; Ethics